Predictions of diabetes complications and mortality using hba1c variability: a 10-year observational cohort study - Lee, Sharen; Liu, Tong; Zhou, Jiandong; Zhang, Qingpeng; Wong, Wing Tak; Tse, Gary (Acta diabetologica, 2021)
Introduction Emerging evidence suggests that HbA1c variability, in addition to HbA1c itself, can be used as a predictor for mortality. The present study aims to examine the predictive power of mean HbA1c and HbA1c variability measures for diabetic complications as well as mortality. Methods The retrospective observational study analyzed diabetic patients who were prescribed insulin at outpatient clinics of the Prince of Wales Hospital and Shatin Hospital, Hong Kong, from 1 January to 31 December, 2009. Standard deviation (SD), root mean square (RMS), and coefficient of variation were used as measures of HbA1c variability. The primary outcomes were all-cause and cardiovascular mortality. Secondary outcomes were diabetes-related complications. Results The study cohort consists of 3424 patients, including 3137 patients with at least three HbA1c measurements. The low mean HbA1c subgroup had significantly shorter time-to-death for all-cause mortality ( P < 0.001) but not cardiovascular mortality ( P = 0.920). The high Hba1c subgroup showed shorter time-to-death for all-cause ( P < 0.001) and cardiovascular mortality ( P < 0.001). Mean Hba1c and Hba1c variability predicted all-cause as well as cardiovascular-specific mortality. In terms of secondary outcomes, mean HbA1c and HbA1c variability significantly predicted diabetic ketoacidosis/hyperosmolar hyperglycemic state/diabetic coma, neurological, ophthalmological, and renal complications. A significant association between dichotomized HbA1c variability and hypoglycemia frequency was found ( P < 0.0001). Conclusion High HbA1c variability is associated with increased risk of all-cause and cardiovascular mortality, as well as diabetic complications. The association between hypoglycemic frequency, HbA1c variability, and mortality suggests that intermittent hypoglycemia resulting in poorer outcomes in diabetic patients.